Layer-by-layer assembled micro and nano carriers for drug delivery applications - Mutukumaraswamy Shaillender (2013)
In nano- or microparticulate drug delivery, both control of the drug release and interaction of the particles with the cellular environment are critical attributes. Polyelectrolyte layering of the particle surface offers an interesting and facile way to modulate both attributes. Layer-by-Layer (LbL) technology involves the consecutive assembly of oppositely charged polyelectrolytes based on electrostatic interactions onto charged template surfaces. The relative ease of preparation through the LbL self- assembly, accurate control over the wall thickness as well as the flexibility in the choice of constituents qualifies these carriers to constitute an influential domain in the field of particulate technology. The bioactive agents may either be encapsulated in the core/template or inside the multilayers, with the option to tailor the properties of the carrier to the specific needs of the active material and therapeutic application. Despite having great potential in the design of versatile LbL carriers, there are very few studies that report the design of carriers suitable for drug delivery applications. In particular, the characterization and applications of biodegradable, biocompatible carriers, coated with polyelectrolyte multilayers, have not been extensively studied to date